A Paradox in Consumer Shopping Behavior towards Digital Technologies in Brick Stores: An Experimental Approach - Shanmugarajah , Vithyalega; Achchuthan, Sivapalan; Prahalathan , Balasingam; Umakanth , Natkunarajah (Asian Journal of Empirical Research, 2018)
The main focus of this research is to analyze how digital in brick stores can affect the shopping experience. The study conveys new insights to the retailers to devise their digital strategy in the brick stores instead of blindly following a paradigm shift. As the previous studies of this research field has limitations in measuring the exact impact of digital due to variance of other factors, it was decided to use scenario based experiments. It was concluded that customers prefer to be served by service personnel than digital devices and only in the cases where the waiting time is more, customers prefer digital services. The more the utilitarian and hedonic values are given by a retailer, the more that shopping experience would be perceived as the best. Rather than following a digital paradigm, it is time for the retailers to take a pause and think how to differentiate themselves considering the customers’ expectations to create a better shopping experience. To this end, a conceptual framework for shopping experience is created to summarize the results of this research study which can facilitate the retailers to create a wholesome shopping experience.